2017
DOI: 10.14720/aas.2017.109.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Response of onion to different nitrogen levels and method of transplanting in moderately salt affected soil

Abstract: Rapid increase in population and consumption, urged upon the agronomists to develop a comprehensive site specific agro technology to boost up production per unit area and quality of daily dietary onion crop in salt affected soils by improving some basic components of the prevailing onion production technology in Pakistan. In this perspective a detailed and systematic series of field studies were undertaken for three consecutive years (2013 -2015) at Soil Salinity Research Institute, Pindi Bhattian, Pakistan t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Khokhar [12] also reported that long days and high temperatures promote onion bulb formation. The authors [13][14][15]18,20] reported similar results.…”
Section: Buld Diametersmentioning
confidence: 56%
See 1 more Smart Citation
“…Khokhar [12] also reported that long days and high temperatures promote onion bulb formation. The authors [13][14][15]18,20] reported similar results.…”
Section: Buld Diametersmentioning
confidence: 56%
“…The highest onion yield and maximum yield attributes including plant height, number of leaves per plants, diameter of bulb, bulb mass and total bulb yield were recorded with nitrogen application at the rate of 135 kg/ha and 112.2 kg/ha in ridge planting. The highest economic return was recorded for nitrogen application at the rate of 112.5 kg/ha in ridge planting [20].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have also been carried out to evaluate the effect of N levels on the growth and yield of onions. Applied N doses fluctuate from about 50 to above 200 kg•ha −1 , depending on the region, type of growing onion, and other production practices, like irrigation [22]. For instance, Abdissa et al [23] found the application of 69 kg•N•ha −1 to be adequate for the growth and bulb yield of onions in Shewa Robit, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%